2017
DOI: 10.33260/zictjournal.v1i1.9
|View full text |Cite
|
Sign up to set email alerts
|

ICT as an Enabler to Academic Success of Students with Visually Impaired at Sim University

Abstract: While the World Health Organisation’s (WHO) benchmark is 15.6 percent, ‘Sim’ (pseudonym) University is way below that benchmark as only 0.001 percent are students classified as ‘disabled’ despite being in existence for more than 50 year. Within the 0.001, students with visually impaired (SwVI) are the majority estimated at 70 percent. In the 21st century, ICTs generally serve as catalysts to academic success of students in Universities. Therefore, the purpose of this study was to explore the role played by Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
1
10
0
Order By: Relevance
“…The remaining 5% of learners were mostly learners with albinism who use some large print in some schools. This is consistent with Simui, Kasonde-Ngandu and Nyaruwata's [7] study findings on ICTs as enablers to academic success of leaners with visual impairments in Sub-Saharan Africa. In their study, it was observed that learners with visual impairments actively applied ICTs such as typewriters, cell phones, elevators with speech facility, computers, jaws, e-mails and talking watches among others for academic purposes.…”
Section: Introductionsupporting
confidence: 91%
“…The remaining 5% of learners were mostly learners with albinism who use some large print in some schools. This is consistent with Simui, Kasonde-Ngandu and Nyaruwata's [7] study findings on ICTs as enablers to academic success of leaners with visual impairments in Sub-Saharan Africa. In their study, it was observed that learners with visual impairments actively applied ICTs such as typewriters, cell phones, elevators with speech facility, computers, jaws, e-mails and talking watches among others for academic purposes.…”
Section: Introductionsupporting
confidence: 91%
“…The government should embrace at all costs the need to invest in technologies that help inclusion to be real if Zambia is to move forward with the inclusive education agenda. Currently, studies on inclusive education in Zambia show that learners have no access to computers and other ICTs that facilitate access to the curriculum (Simui, Kasonde-Ngandu and Nyaruwata, 2017;& Mtonga, 2013). ICTs increase participation in learning and access to the curriculum.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Thus, there was need to ride on reflective practice as a critical tool to empower teachers to welcome diversity and challenge disablers in their learning contexts [48] & [49]. Equally, ICTs were recommended as enablers to academic success of learners for inclusive education [50].…”
Section: International Perspectives On Preparing Preservice Teachersmentioning
confidence: 99%